1997
DOI: 10.1021/ic961226z
|View full text |Cite
|
Sign up to set email alerts
|

cis-Dichloro(α,ω-diamino carboxylate ethyl ester)palladium(II) as Palladium(II) versus Platinum(II) Model Anticancer Drugs:  Synthesis, Solution Equilibria of Their Aqua, Hydroxo, and/or Chloro Species, and in Vitro/in Vivo DNA-Binding Properties

Abstract: cis-Dichloro(d,l-2,3-diaminopropionate ethyl ester)palladium(II), cis-[Pd(Etdap)Cl(2)] (I), and cis-dichloro(d,l-2,4-diaminobutyrate ethyl ester)palladium(II), cis-[Pd(Etdab)Cl(2)] (II), were synthesized and characterized by elemental analysis, IR spectroscopy, and TG-DTA thermal analysis. The equilibrium model and log beta(pqr) constants of hydrolytic species of I and II were also investigated by potentiometric methods (I = 0.15 M (NaClO(4)) and 37 degrees C). Aqueous solutions of cis-[Pd(Etdaa)(H(2)O)(2)](Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Platinum complexes PtCl 2 (dap-Metala), PtCl 2 (dabMetala), PtCl 2 (dap-phe) and PtCl 2 (dab-phe) were synthesized using equimolar ratios of K 2 PtCl 4 and diamine chelating ligands, following a method adapted from Inagaki et al [49] and Gonzalez et al [50] (Scheme 2). As free diamine chelating ligands were present as amine salts, a neutralization with NaHCO 3 was necessary prior to platination.…”
Section: Synthesis and Chemical Characterizationmentioning
confidence: 99%
“…Platinum complexes PtCl 2 (dap-Metala), PtCl 2 (dabMetala), PtCl 2 (dap-phe) and PtCl 2 (dab-phe) were synthesized using equimolar ratios of K 2 PtCl 4 and diamine chelating ligands, following a method adapted from Inagaki et al [49] and Gonzalez et al [50] (Scheme 2). As free diamine chelating ligands were present as amine salts, a neutralization with NaHCO 3 was necessary prior to platination.…”
Section: Synthesis and Chemical Characterizationmentioning
confidence: 99%
“…It has been observed that the complexes [Ru(j 3 -L)(EPh 3 )Cl 2 ] (E = P, As; L = tpy and tptz) containing both the EPh 3 and polypyridyl ligands behave as good precursors and act as metallo-ligands in the syntheses of homo-/hetero-bimetallic complexes [17,18]. Also, these behave as inhibitors of Topo II and heme polymerase activity.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of complexes containing a-amino acids has become increasingly important due to their significant role in biological fields [19,20]. The amino acids are known to bind metal ions as a bi-dentate N,O-donor ligand forming five membered chelate rings after dissociation of the acidic proton [17,18]. It is noteworthy that while the chemistry of many transition metal complexes containing amino acids has been studied in detail, the chemistry of ruthenium complexes has received only little attention [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in this area have focused on Pd(II) complexes with one N,N-diamino [17][18][19][20] or N,S-aminothioether [21][22][23] chelating ligand that impels cis-coordination with more labile ligands (containing two chlorine or nitrate moieties or one dicarboxylate moiety). In such cases, the chelating ligand prevents cis-trans isomerization around Pd(II) in spite of its greater lability (about 10 5 -fold) relative to its Pt(II) [13,17,24] analogs.…”
Section: Introductionmentioning
confidence: 99%